2013
DOI: 10.1542/peds.2013-1227
|View full text |Cite
|
Sign up to set email alerts
|

Spanking and Child Development Across the First Decade of Life

Abstract: WHAT'S KNOWN ON THIS SUBJECT: A large and growing literature has demonstrated significant associations between the use of spanking and later child aggression, but we know less about paternal spanking, effects of spanking on cognitive development, and longer-term effects.WHAT THIS STUDY ADDS: Accounting for a broad array of risk factors, spanking predicts both aggression and receptive vocabulary across the first decade of life. Importantly, we include paternal spanking, cognitive outcomes, and a longitudinal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(77 citation statements)
references
References 23 publications
(14 reference statements)
3
71
1
Order By: Relevance
“…A growing body of empirical research indicates that spanking is associated with the development of children's aggressive and antisocial behavior (Berlin et al, 2009;Gershoff, 2002;Grogan-Kaylor, 2004;Lansford et al, 2011;MacKenzie et al, 2013;Maguire-Jack et al, 2012). A recent FFCWS study showed that early maternal spanking is linked to children's behavioral problems through the first decade of life (MacKenzie et al, 2013).…”
Section: Transactional Models Across the First Five Yearsmentioning
confidence: 99%
See 3 more Smart Citations
“…A growing body of empirical research indicates that spanking is associated with the development of children's aggressive and antisocial behavior (Berlin et al, 2009;Gershoff, 2002;Grogan-Kaylor, 2004;Lansford et al, 2011;MacKenzie et al, 2013;Maguire-Jack et al, 2012). A recent FFCWS study showed that early maternal spanking is linked to children's behavioral problems through the first decade of life (MacKenzie et al, 2013).…”
Section: Transactional Models Across the First Five Yearsmentioning
confidence: 99%
“…A recent FFCWS study showed that early maternal spanking is linked to children's behavioral problems through the first decade of life (MacKenzie et al, 2013). One reason for this link may be that parents' use of spanking models the use of aggression to solve problems (Bandura, 1973), and children imitate their parents' use of aggression to solve their own conflicts or disagreements with peers and siblings.…”
Section: Transactional Models Across the First Five Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corporal punishment negatively affects the internalization of moral values by the child and his relationship with his parents [15]. Physical punishment is linked to a slow regression of cognitive development as well as negative effects on the academic pathway [1620], noncognitive performance and executive functions [21] as well as alterations in the dopaminergic regions associated with substances and alcohol abuse [22]. In particular, negative experiences in childhood predispose later in life, to multiple sexual partners, sexually transmitted diseases, teenage pregnancies, unwanted pregnancies, and early initiation of sexual activity [23].…”
Section: Introductionmentioning
confidence: 99%